Burnout syndrome in nursing professionals in the context of the COVID-19 pandemic - Priscila Moreira de Souza; José Gerfeson Alves; Glícia Uchôa Gomes Mendonça; Moziane Mendonça de Araújo; Camila Fonseca Bezerra; José Wagner Martins da Silva; Olga Feitosa Braga Teixeira (Rev Rene, 2023)
Objective: to investigate the prevalence of Burnout Syndrome in nursing workers during the COVID-19 pandemic. Methods: cross-sectional study using instruments to collect sociodemographic and professional data and the Maslach Burnout Inventory. The population was formed by 52 nursing workers from three institutions that attend patients with COVID-19. The sampling was by convenience, and workers were contacted via email or WhatsApp®. We compared the means of each domain using Student's t-test, considering the variables from the Maslach Burnout Inventory, namely, emotional exhaustion, depersonalization, and effectiveness at work. Results: the overall mean Burnout was 3.21. The differences between the means of emotional exhaustion and personal accomplishment domains were significant for the variables "would change jobs” (p<0.04) and “job satisfaction” (p<0.001). Conclusion: Workers had a high level of Burnout, being thus susceptible to mental suffering and psychic disease: Contributions to practice: the knowledge produced here can provoke reflections that will help develop and apply strategies to reduce the negative impact of the Burnout Syndrome in the health of the nursing professional.